Heme Oxygenase Gene Targeting to Adipocyte Attenuates Adiposity and Vascular Dysfunction in Mice Fed a High Fat Diet - Cao, Jian (2012)
We examined the hypothesis that adipocyte dysfunction in mice fed a high fat (HF) diet can be prevented by lentiviral-mediated and adipocyte specific-targeting delivery of the human heme oxygenase-1 (aP2-HO-1). A bolus intracardial injection of aP2-HO-1 resulted in expression of human HO-1 for up to 9.5 months. Transduction of aP2-HO-1 increased human HO-1 expression in fat tissues without affecting murine HO-1. In mice fed a HF diet, aP2-HO-1 transduction attenuated the increases in body weight, blood glucose, blood pressure and inflammatory cytokines as well as the content of both visceral and subcutaneous fat. Transduction of aP2-HO-1 increased the numbers of adipocytes of small cell size (p<0.05), insulin sensitivity (p<0.05),adiponectin levels as well as vascular relaxation to acetylcholine compared to HF mice administered the aP2-Green Fluorescent Protein (aP2-GFP). Adipocytes of mice fed a HF diet expressed high levels of PPARγ, aP2, C/EBP and Wnt5b proteins and displayed marked increases in Peg1/Mest (p<0.03). Transduction of aP2-HO-1 lowered the elevated levels of these proteins and increased Shh, Wnt10b and β-catenin (p<0.05). Inhibition of HO activity by administration of tin mesoporphyrin (SnMP) to HF-fed mice transduced with the aP2-HO-1 reversed the decrease in Peg 1/Mest, TNFα and MCP-1 levels. Collectively, this novel study demonstrates that adipocyte-specific overexpression of HO-1 attenuates HF-mediated adiposity and vascular dysfunction, increases insulin sensitivity and improves adipocyte function by increasing adiponectin, Shh and WNT10b and decreasing inflammatory cytokines.